2021
DOI: 10.3390/nano11051066
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoclusters Display Low Immunogenic Effect in Microglia Cells

Abstract: Gold nanoparticles hold a great promise for both clinical and preclinical applications. The major factors impeding such applications are toxicity of new nanomaterials including e.g., pro-apoptotic activities or inflammatory effects, but also their potential to accumulate in the body or inadequate absorption, distribution, metabolism and excretion (ADME) profiles. Since such adverse effects depend on the size, form and coating of nanomaterials, the search for new, less toxic nanomaterials with low tendency to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Depending on the nanoclusters size and structure, it can be located from blue to near infrared (NIR), the most attractive region in terms of bioimaging applications. Recent studies on toxicity and biodistribution of Au 18 (SG) 14 in in vivo systems show promising results and are the first step to utilizing nanoclusters for bioimaging and biosensing applications [ 20 , 21 , 22 ]. Nanoclusters are well-characterised under one-photon excitation, but also present excellent nonlinear optical properties, which can be utilized in two-photon imaging [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the nanoclusters size and structure, it can be located from blue to near infrared (NIR), the most attractive region in terms of bioimaging applications. Recent studies on toxicity and biodistribution of Au 18 (SG) 14 in in vivo systems show promising results and are the first step to utilizing nanoclusters for bioimaging and biosensing applications [ 20 , 21 , 22 ]. Nanoclusters are well-characterised under one-photon excitation, but also present excellent nonlinear optical properties, which can be utilized in two-photon imaging [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the synthesis of metal nanoclusters of different sizes is worthy of a systematic study in order to broaden their application scope. Similarly, as we discussed above, the surface chemistry of NCs also plays a crucial role in altering their properties and stability. Further understanding of the fundamental principles underlying the tailoring of metal NCs to obtain excellent properties is required in future research. …”
Section: Conclusion and Perspectivementioning
confidence: 94%
“…They consist of 18 atoms of gold and are stabilized with glutathione ligands. The authors of this study showed that these Au18 gold nanoclusters (NCs) have, at low concentrations, anti-inflammatory signaling (reduction of (IL1-β) levels, unchanged levels of TNF-α or Ym1/2) but, at higher concentrations, they can have pro-inflammatory activity [ 75 ]. The authors suggested that the presence of glutathione could be the source of this anti-inflammatory activity.…”
Section: Brain Nanomedicine and Microgliamentioning
confidence: 99%